2017
DOI: 10.18203/2320-6012.ijrms20174605
|View full text |Cite
|
Sign up to set email alerts
|

Delay in diagnosis of breast cancer in a developing country: a single centre observational study in a tertiary care hospital in North Kerala, India

Abstract: Background: Around the world breast cancer is the most common cancer in women. In India, peak incidence is between 45-50 years of age. Early diagnosis improves survival, hence reducing diagnostic delay in breast cancer will have major social and economic implications besides improving the quality of life. This observational study aims to decipher various factors influencing diagnostic delay so that early treatment can be instituted.Methods: We interviewed 212 consecutive patients who attended the twice weekly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
(9 reference statements)
2
3
0
Order By: Relevance
“…In the present study about 60% were in early stage which is consistent with other studies from Kerala [29,8], and in contrast to Northern parts of India where only 46% presented in early stages [9].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study about 60% were in early stage which is consistent with other studies from Kerala [29,8], and in contrast to Northern parts of India where only 46% presented in early stages [9].…”
Section: Discussionsupporting
confidence: 93%
“…In this study, work ability is measured using the Work Ability Index (WAI) [17], a valid and well accepted tool for perceived work ability of individuals. It includes seven items, with scores ranging from 7-49 with further categorisation into poor , moderate (28)(29)(30)(31)(32)(33)(34)(35)(36), good (37)(38)(39)(40)(41)(42)(43), and excellent (44-49) [18]. The seven dimensions include current work ability compared to lifetime best, current work ability in relation to demands of the work, number of comorbidities, current work impairment due to the disease, absenteeism, own prognosis of work ability two years from now, and estimate of their mental resources.…”
Section: Methodsmentioning
confidence: 99%
“…As noted in previous reports from Iraq (19,26) , it was found in this study that the greater proportion of those who practiced self-examination was observed among the highly educated and employed sector of the community. Consistent findings were recorded in previous studies (19)(20)(21)(22)26,27) . Family history of breast cancer was displayed in 46% of the studied cases and the breast was involved in 33.5%.…”
Section: Discussionsupporting
confidence: 92%
“…In the current study it was observed that only 5.5% of the patients had performed regular BSE on monthly basis before they were diagnosed with the disease, 57.5% had practiced that method randomly while 37% revealed no history of previous experience with that technique. In another observational study carried out on breast cancer patients treated in a tertiary care hospital in India it was found that 32% have practiced BSE (21) . A recently published survey was organized by the INCRC to assess the baseline needs for breast cancer awareness, correlating the findings among patients affected by breast cancer during the treatment phase with the corresponding healthy controls to address their level of knowledge, beliefs and behavior towards the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Awareness about the disease however, 2570 so on (Unger-Saldaña, 2014). This finding has been further reiterated through numerous studies conducted in India (Babu et al, 2013;Sathwara et al, 2017;Lakshmanan et al, 2017). In addition to the lack of an organised screening programme in the country, numerous sociocultural barriers seem to play an important role in further dissuading women from getting timely screening or treatment (Singh et al, 2015;Yip, 2016).…”
Section: Introductionmentioning
confidence: 99%